2018
DOI: 10.2139/ssrn.3275526
|View full text |Cite
|
Sign up to set email alerts
|

Able but Unwilling to Enforce: Cooperative Dilemmas in Group Lending

Abstract: It is known that greater social cohesion increases a group's ability to enforce cooperation. Despite this, defectors often go unpunished, and groups with social structures that are a priori favorable often fail. A critical distinction is required between the structural effect on ability versus willingness to punish. The authors develop a theoretical framework in which variation in a group's social structure generates a tension between ability and willingness to enforce cooperation. Structures that promote abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…These findings show that relatives and friends do not want to be in dispute with other members. This argument is also in line with Sabin and Reed-Tsochas (2020) findings, providing mixed methods evidence from group-based lending schemes in Sierra Leone. They find that members of socially cohesive (tied) group members are unwilling to punish other group members when they do not repay their loans although they can punish them.…”
Section: Resultssupporting
confidence: 86%
“…These findings show that relatives and friends do not want to be in dispute with other members. This argument is also in line with Sabin and Reed-Tsochas (2020) findings, providing mixed methods evidence from group-based lending schemes in Sierra Leone. They find that members of socially cohesive (tied) group members are unwilling to punish other group members when they do not repay their loans although they can punish them.…”
Section: Resultssupporting
confidence: 86%
“…We report associations as positive, negative or non-significant in accordance with the original authors' own most permissive significance cut-offs (p<0.1 in the majority of studies; SM1). In all studies, only monotonic relationships between predictors and repayment efficacy were analysed, except for two studies (Kolstad et al, 2017;Sabin and Reed-Tsochas, 2018), which reported an inverted U-shaped relationship between a predictor and repayment efficacy. Thus, in the results, "Inverted U" is reported as an extra category.…”
Section: Extraction Of Effects Of Predictors On Repayment Efficacy Frmentioning
confidence: 99%
“…The observation that kinship can generate collusion (i.e., cooperation) within the loan group against the MFI suggests that other factors which increase within-group cohesion may similarly reduce repayment efficacy. For example, a decrease in repayment was observed in a microcredit program in Sierra Leone when groups were "too cohesive", measured by their geographical proximity (Sabin and Reed-Tsochas, 2018). When penalties by the lender are too small, cooperation for repayment at the loan-group level may be less relevant than cooperation at other levels, such as the household, neighbourhood, community or dyad.…”
Section: The Negative Effect Of Common Ancestrymentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that repayment under JLL is a cooperative dilemma requiring collective action has long been recognised by social scientists (Anthony, 2005;Guttman, 2007;Sabin and Reed-Tsochas, 2018;van Bastelaer and Leathers, 2006), but it is not always treated explicitly as such in group lending models. For example, the seminal economic model of group lending by Besley and Coate (1995) assumes that borrowers employ sanctions to oblige other group members to repay their shares, making repayment the self-interested choice.…”
mentioning
confidence: 99%